Polymeric systems as nanodevices for siRNA delivery - Tiera, Marcio J. [UNESP]; Shi, Qin; Barbosa, Hellen Franciane Gonçalves [UNESP]; Fernandes, Julio C. (Bentham Science Publishers, 2013)
The delivery of small interfering RNAs (siRNAs) is a promising approach to silencing gene expression aimed at treating infections, cancer, neurodegenerative diseases and various other disorders. Recent progress in this area has been achieved with nanodevices possessing multiple properties and assembled with new, biodegradable, synthetic polymers and polysaccharides. Different synthetic routes and multiple strategies, such as multilayer systems and stimuliresponsive polymers, have been developed to attain high efficiencies. This review covers the most important, promising and successful approaches to improve siRNA delivery. It is a concise report on multiple strategies employed, including cell-specific delivery coupling ligands or antibodies with nanodevices to improve siRNA efficiency and specificity. © 2013 Bentham Science Publishers.
Keywords: Gene therapy; Multifunctional; Nanoparticles; Polycations; Sirna delivery; Stimuli-responsive polymers